Effects of dehydroepiandrosterone on in vivo ovine follicular development - Narkwichean, Amarin; Jayaprakasan, Kannamannadiar; Maalouf, Walid E.; Hernandez-Medrano, J.H.; Pincott-Allen, Catherine; Campbell, Bruce K. (Oxford University Press, 2014)
STUDY QUESTION: What are the effects of exposure of ovarian tissue to dehydroepiandrosterone (DHEA) supplementation in vivo? SUMMARY ANSWER:DHEA exposure stimulates initiation of primordial follicles and development of gonadotrophin-responsive preantral/early antral follicles possibly mediated through promoting granulosa cell proliferation and enhancing anti-Mullerian hormone (AMH) expression. WHAT IS KNOWN ALREADY? Ovarian ageing is a cause of subfertility and is associated with poor outcomes of IVF treatment and premature menopause. A few clinical studies have shown that DHEA can improve ovarian response and increase the chances of pregnancy after IVF treatment in women with a diminished ovarian reserve (DOR) suggesting DHEA may help to overcome the effect of ovarian ageing. However, there are no data about how DHEA acts on ovarian folliculogenesis. STUDY DESIGN, SIZE AND DURATION: A cortical autograft experimental model was conducted in six female sheep aged at least 24 months. The period of DHEA treatment in the animals lasted for 10 weeks. PARTICIPANTS/MATERIALS, SETTING, METHODS: All the animals were subjected to unilateral oophorectomy. Half of the ovary was fixed for histological analysis as a time-zero control. The remaining tissue was used to isolate patches of ovarian cortex which were autografted back onto the ovarian pedicle. The grafting procedure eradicated all growing follicles and synchronized early follicular development. After a 10-week treatment period with DHEA implants, the ewes were sacrificed and the graft and remaining ovary were harvested. Histological and immunohistochemistry (IHC) findings, accompanied with serum hormonal profiles were compared to determine the effect on the follicle population. MAIN RESULTS AND THE ROLE OF CHANCE: Higher proportions of the follicle population in the remaining ovary were observed to be in the antral stage after DHEA treatment. The observation coincided with an increase in the rate of primordial follicle initiation and preantral follicle development in cortical grafts and the remaining ovarian tissue, respectively. The IHC results indicated that DHEA increased the expression of both the proliferation marker (KI-67) in granulosa cells and the follicular AMH expression at the preantral and early antral follicle stages. LIMITATIONS, REASONS FOR CAUTION: The experimental design compared follicle populations before and after DHEA treatment within individual animals to allow changes over time to be detected against a background of high inter-animal variation. However, since no controls without DHEA were included, we cannot say what would have happened over time in its absence, and it is possible that other factors may have resulted in the changes in follicle development observed during the experiment. WIDER IMPLICATIONS OF THE FINDING: Our data supports the idea that DHEA might be a useful therapy to delay the effects of ovarian ageing. Therefore, it may have a role as an adjunct during IVF to improve ovarian response in women with DOR and as a treatment for premature ovarian insufficiency.